Prevalence of Skin Diseases in Kavre District, Nepal - Karn, D; Khatri, R; Timalsina, M (Nepal Journal of Dermatology, Venereology & Leprology, 2012)
Background Skin is the major interface of human to the environment . It is the major susceptible organ for any disease. Wide prevalence of skin diseases in the community is a well established fact. Objectve The aim of this study is to determine the prevalence of skin diseases among the general population of Kavre District,Nepal . Methods This is a hospital based, retrospective study done among all the patients visiting Dhulikhel Hospital, Kathmandu University Teaching Hospital, in Dhulikhel, Kavre during the year 2007-2008 AD. Data were obtained from the hospital out-patient records and analyzed. The total number of patients who visited the hospital were 74,279 (male-30,809 female- 43,470), out of which 7374 (9 .92 %), male 4155, female 3219, visited the Dermatology Department. Among this total study population now comparative study of the prevalence of skin diseases was performed based on sex, age and type of dermatological condition. Results The overall prevalence of skin diseases were 9.92% with slight higher rates seen among males ( 56.34 %) than females (43.65 %).Non-infective conditions , 6063 ( 82.22% ) outweighed infective conditions 1311 (17.78 %), commonest one being the pigmentary disorders (32.56 %) and in the age group 16-35 years old (31.23% ). Conclusion This study demonstrates that skin diseases are one of the most prevalent disease condition among the general population, representing a major public health problem. Keywords Prevalence; infective diseases; non-infective diseases. DOI: http://dx.doi.org/10.3126/njdvl.v9i1.5761 NJDVL 2010; 9(1): 7-9